Efektivitas Foot Massage Dengan Essential Oil Lavender dalam Mengatasi Gangguan Pola Tidur Lansia di UPT Pelayanan Sosial Tresna Werdha Banyuwangi - Diana Balqis, Rani; Paramitha, Ni Kade Wahyu (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2025)
Objective: Disruption of sleep patterns is a disturbance that occurs in the quality and quantity of a person's sleep time due to external factors. Decreasing the quality of sleep in the elderly will have a negative impact on health. One of the therapies to treat sleep pattern disturbances non-pharmacologically is to use Foot Massage therapy with lavender essential oil. Foot Massage is known for its relaxing properties, while lavender oil is recognized for its calming effects and its ability to combat insomnia, so massage therapy using lavender essential oil can be done to improve sleep pattern disturbances in the elderly. Methods: The case study method was used in this study by providing nursing care which included assessment, diagnosis, intervention and implementation of Foot Massage with Lavender Essential Oil carried out for 15 minutes before the patient went to sleep and evaluation of the client's sleep quantity. Results: Foot Massage with lavender essential oil is routinely done for 15 minutes before the patient goes to bed. There was a change in the quality of sleep after Foot Massage with lavender essential oil, namely sleep time to 7 hours from less than 5 hours previously. Conclusion: It can be concluded that there exists significant influence of Foot Massage and lavender essential oil on the elderly who experience sleep pattern disturbances. The results of this scientific work can be used as input for the Tresna Werdha